Perawatan kaping pulpa indirek disertai restorasi resin komposit pada premolar kedua kanan maksila - Moniaga, Winny; Elline; Elsa Prahasti, Anastasia; Ratnasari, Dina (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Dental caries remains a common condition among people of all ages, as indicated by its impact on the elderly and young people. Proximal caries become more prevalent and eventually dominate the decayed filled surfaces (DFS) score The current restorative dentistry technique aims to induce remineralization of hypomineralized carious dentine, thus conserving and preserving the vital pulp, it could reduce the need for more invasive endodontic therapy. Unexposed pulp with minor inflammation from traumatic injuries or cavities has a good chance of being repaired, It is predicted that pulp tissue will have a repair capacity following removal of a caries lesion. The goal of indirect pulp therapy is to preserve tooth life by regenerating reparative dentin at the material-pulpal complex, which functions as a biological seal.Case report: A 26-year-old male patient presented to the endodontic and conservative dentistry department complaining of discomfort caused by thermal stimulation on the permanent maxillary right premolar and molar. The radiograph examinations revealed no radiolucencies in the periapical region and an interproximal caries lesion on the maxillary right second premolar and first molar with a deep distal caries lesion on the secondary premolar, close to the pulp. Thermal pulp vitality testing confirmed the sensitivity of the pulp. The treatment approach was devised to maintain the vitality of the pulp. Infected dentin was removed and lined with a calcium silicate-based substance, followed by the placement of composite resin as a final restoration.Conclusion: Using light-cured calcium silicate material showed advantages in clinical performance as an indirect pulp capping agent.